A 7 YEAR-7-MONTH OLD BOY WITH LEUKEMIC RETINOPATHY - Rini Suari, Ni Made; **, Widnyana; Budhiastra, Putu (Medicina; Vol 44 No 1 (2013): Januari 2013)
Normal 0 false false false IN X-NONE X-NONE MicrosoftInternetExplorer4 Ocular problems in patient with leukemia which are called leukemic retinopathy and subhyaloid hemorrhage is one of its feature. Subhyaloid hemorrhage in children with acute lymphoblastic leukemia (ALL) is rarely happened. We reported a boy 7 year 7 month old, complained sudden blurred vision on his both eyes and diagnosed with acute lymphoblastic leukemia. When patient had complained his vision, result of routine hematology showed anemia, thrombocytopenia, and leukocytosis. Treatment of leukemic retinopathy in this patient was supportive and causal therapy with transfusion of thrombocyte concentrate, hydration for leukocytosis, giving chemotherapy intrathecal methotrexate and systemic (vincristine, daunorubicin, L-asparginase). We found gradually undergone resolution of subhyaloid hemorrhages, visible flame shaped thin, and his vision recovered nearly completely to 6/6 OD and 6/20 OS /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: children, leukemic retinopathy, acute lymphoblastic leukemia